Digital Skills To Improve Work Performance - Mila Sartika; Sih Darmi Astuti; Amalia Nur Chasanah; Fery Riyanto (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2023)
Workers in the manufacturing sector face the need to acquire digital skills to improve work efficiency and productivity. However, the rapid and intense spread of technology has also caused technostress and the phenomenon where the stress associated with the use of technology can disrupt the work performance This study uses questionnaires in data collection. The number of samples is 102. The variables used in this study are Digital Skill and Technostress as independent variables and Employee Performance variables as dependent variables. Data processing techniques using Smart PLS. Digital skills and technostress have a significant positive effect on employee performance. This research underscores the importance of digital skills and the potential impact of technostress on employee performance. Organizations should prioritize digital skill development initiatives and consider strategies to mitigate technostress among employees.